True happiness in the presence of YHWH: The literary and theological context for understanding Psalm 16 - Botha, Phil J. (Old Testament Essays, 2016)
This article attempts to interpret Ps 16 as part of the cluster of Psalms 15-24, but also as a Torah-wisdom psalm. Hossfeld and Zenger have argued that Ps 16 was added to this cluster simultaneously with Pss 19 and 23, but that this happened quite some time before Ps 1 was composed to serve (together with Ps 2) as the preface to the whole Psalter. It is proposed here that Ps 16 is a Torahwisdom composition which exemplifies true blessedness as compliance with the Torah of YHWH in contentedness with one's lot in life. It thus represents the kind of piety also portrayed in other Torahwisdom psalms such as Pss 1, 19, 23 and 73. It is consequently suggested that Ps 16 is much closer to Ps 1 in time of origin and teaching as has been accepted until now. This does have implications for its interpretation.
free